Use of Repeated Within-Subject Measures to Assess Infants’ Preference for Similar Others - Cruz-Khalili, Amir; Bettencourt, Katrina; Kohn, Carolynn S.; Normand, Matthew P.; Schlinger, Henry D. (Frontiers in Psychology, 2019)
Research employing single-choice paradigms in which an infant is asked to make a single choice between two puppets suggest that infants show a preference for prosocial others and those who are similar to themselves. However, the extent to which infants’ preference for similar others is stable is unknown, as are other factors within the paradigm that may influence infants’ choice. The purpose of this study (two experiments, N = 44 infants, aged 8 to 15 months) was to replicate and extend previous work by including (a) within-subject repeated measures and (b) an experimental manipulation of a plausible demand characteristic. Results for the first-choice trial indicated a majority of the infants did not choose the similar puppet. Results from the within-subject repeated trials also indicated that a majority of the infants did not choose the similar puppet but a majority did choose a puppet from the same side. The experimental manipulation of the demand characteristic showed no effect on infant puppet choices. These results suggest that a closer examination of the single-choice puppet paradigm for assessing infants’ social evaluation is warranted. These findings also support recommendations made by others, including publishing null findings, standardizing data collection and reporting methods, and examining individual differences by employing within-subject designs with repeated measures.